Human stem cell technology and biology : a research guide and laboratory manual - Stein, Gary S. (Hoboken, N.J. : Wiley-Blackwell, 2011)
'Human Stem Cell Technology & Biology: A Research Guide and Laboratory Manual integrates readily accessible text, electronic and video components with the aim of effectively communicating the critical information needed to understand and culture human embryonic stem cells. Key Features: An authoritative, comprehensive, multimedia training manual for stem cell researchers. Easy to follow step-by-step laboratory protocols and instructional videos provide a valuable resource. A must-have for developing laboratory course curriculums, training courses, and workshops in stem cell biology. Perspectives written by the world leaders in the field. Introductory chapters will provide background information. The volume will be a valuable reference resource for both experienced investigators pursuing stem cell and induced pluripotent stem cell research as well as those new to this field'--Provided by publisher
'Current advances in human stem cell research utilize the latest tools of cell biology, molecular biology, chemistry, biomedical imaging, genomics, proteomics and bioinformatics'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Stem Cells; Cell Culture Techniques -- methods; Stem Cell Research; Technology, Medical -- methods -- Laboratory Manuals; Aufsatzsammlung; Laboratory Manuals